Modified WLS - Path Analysis In The Control Of Cattle Flies And Skin Defects - Muhammad Rizal Zuhdi; Adji Fernandes; Ni Wayan Surya Wardhani; Rosita Hamdan (Cauchy: Jurnal Matematika Murni dan Aplikasi)
The cattle industry has an important role in the economy, especially in providing high-quality cowhide for various industries. However, fly infestation, especially from the Chloropidae and Muscidae families, causes many defects in cattle hides that negatively affect their economic value. This study aims to identify factors that influence the extent of defects in cattle hides, focusing on the role of temperature, humidity, and fly infestation. The study was conducted in a Malang cattle farming center by measuring temperature and humidity, catching flies, and calculating the defect area on cattle skin. Data were analyzed using path analysis using modified weighting with the help of R Studio software. The weights used were modified by including correlation in the weight matrix. The results showed that temperature had a significant effect on increasing the defect area in the cheek area of cattle, while humidity had no significant effect. In the abdominal area, neither temperature nor humidity affected the defect area. Infestations of Chloropidae and Muscidae flies were also shown to contribute to increased defect area in the cheek area, but not in the stomach. Preventive strategies for fly control and protection of cattle skin from temperature extremes are needed, especially in the cheek area.